Diretrizes para elaboração de planos de mobilidade urbana de carga - Bárbara Ribeiro Alves Abreu (2015)
The urban freight distribution is considered an essential activity for the development of cities, for the maintenance of needs and peoples lifestyle. The complexity of urban planning involving this activity is reflected in the interest conflict between the stakeholders and the negative externalities brought to the operation, such as traffic jam, noise and air pollution. Now days, the freight transportation planning has excelled on the world stage due mainly to issues like sustainability and urban mobility. Although the recent focus given to these issues in Brazilian cities, especially after the creation of the Federal Law 12.587/2012, little progress has been made in planning the distribution of goods and implementation of urban logistics solutions in the country. In this context, this work presents guidelines to support the development of Load Urban Mobility Plans and proposes a method to evaluating the degree of development of public policies and municipal actions related to urban distribution of goods. For this, the proposed guidelines were reviewed by the Ministry of Cities in the Reference Booklet for Development of Mobility and Urban Planning with successful city logistic solutions applied in several cities, which allowed to create a new guidelines for distinct classes of cities. It held also an exploratory study which it was possible to characterize the urban transport planning in Brazilian municipalities and validate the evaluation model proposed, applying it for the cities of Belo Horizonte, Contagem and Fortuna de Minas - Minas Gerais (Brazil). The exploratory study has identified a significant deficit in the urban mobility plans, quantitatively. Moreover, it was possible to carry out a comparative evaluation between the three distinct municipalities, highlighting the deficit points to be tackled to improve the planning and operation of the urban freight distribution.